Causes of financial crisis in Thailand : Singapore perspective. - Kang, Leng Hui. (2008)
This report examines the causes of the financial crisis in Thailand that started on 2/7/1997. The causes can be broadly categorised into 2 groups: 1)Internal factors, such as unsustainable current account deficit, incorrect sequencing of the financial reform, insufficient prudential regulation and 2)External factors, such as high external debt and a vulnerable international financial system. Lessons of the Asian financial crisis are also discussed.